Transformation Of The Information Museum Into A Smart Museum - Dewi Puspasari; Achmad Nizar Hidayanto (FKIP, Universitas Palangka Raya, 2023)
The term smart museum has started to emerge in recent years along with the development of digital technology and smart concepts related to the application of technology in helping people in various sectors of life. The concept of a smart museum itself refers to the use of internet of things (IoT) technology such as sensors, wireless networks, digital applications, virtual reality, augmented reality, and smart systems to increase the interactivity, accessibility and involvement of visitors in the museum. Now more and more museums are adopting this smart solution as a way to attract visitors and optimize the visitor experience. In Indonesia, one of the museums that has transformed into a smart museum is the Museum Penerangan. In its efforts to become a smart museum, the Museum Penerangan has several supporting factors such as the number of human resources, technology support, program creativity, and support from top management. However, the main obstacle is funding because it requires a large investment to transform into a smart museum, besides that special human resources are needed to understand the technological needs that match the collection.